Development of optically transparent ZnS/poly(vinylpyrrolidone) nanocomposite films with high refractive indices and high Abbe numbers - Zhang, Quanyuan (2014)
A series of optically transparent ZnS-poly(vinylpyrrolidone) (PVP) nanocomposite films with high refractive indices and high Abbe numbers have been prepared. Mercaptoethanol (ME) capped ZnS nanoparticles (NPs) were introduced into the PVP polymer matrix via simple blending with high nanophase contents. ME-ZnS NPs of around 3 nm were prepared from zinc acetate and thiourea precursors in N,N-dimethylformamide using ME as a capping agent. Transparent nanocomposite films with high refractive indices and high Abbe numbers can be easily prepared by a conventional film casting method. TGA results indicated that the ZnS/PVP nanocomposite films exhibit good thermal stability and the measured contents of ZnS NPs in the films agree well with the theoretical values. The refractive indices and the Abbe numbers of the ZnS/PVP nanocomposite films range from 1.5061 to 1.7523 and 55.6 to 20.4 with the content of ME-ZnS NPs varied between 0 and 80 wt %, respectively.